High-strength low-resistivity conductive packaging material and preparation method thereof

Through the composite technology of nitrogen-doped zinc oxide nanorods and polyacrylic acid matrix, the balance problem between conductive packaging materials is solved, and the high-strength and low-resistivity material performance is achieved, which is suitable for high-demand packaging applications.

CN119591916APending Publication Date: 2025-03-11QINGDAO LAOSHUN POLYMER MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411847751.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When existing conductive packaging materials improve their conductive properties, they often lead to a decline in the mechanical properties of the materials, making it difficult to effectively balance the conductivity and mechanical strength.

Method used

By combining nitrogen-doped zinc oxide nanorods with polyacrylic acid matrix, uniformly dispersed by ultrasonic oscillation and stirring to form a conductive packaging material with high strength and low resistivity.

Benefits of technology

The mechanical strength and conductivity of the material are significantly improved, especially in terms of compressive and tear resistance, and maintain good stability and environmental adaptability during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591916A_ABST
    Figure CN119591916A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength low-resistivity conductive packaging material and a preparation method thereof, and relates to the technical field of packaging materials.The preparation method comprises the steps that firstly, zinc oxide nanorods are cleaned and dispersed in deionized water through ultrasonic concussion, urea is added for nitrogen doping treatment, and finally nitrogen-doped zinc oxide nanorods are obtained through cleaning and drying; secondly, polyacrylic acid is dissolved in deionized water, and a polyacrylic acid solution is obtained; and finally, mixing the nitrogen-doped zinc oxide nanorod with a polyacrylic acid solution, adding a dispersing agent sodium dodecyl benzene sulfonate, and ensuring uniform dispersion through ultrasonic oscillation and stirring. The nitrogen-doped zinc oxide nanorod is compounded with a polyacrylic acid matrix, so that the balance between conductivity and strength is remarkably improved, and the pressure resistance and tear resistance of the material are improved. Meanwhile, the dispersity and the conductivity of the zinc oxide nanorod are enhanced through nitrogen doping, the problem that a traditional material is poor in dispersity is solved, and the stability and the long-term use performance of the composite material are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, and in particular to a high-strength and low-resistivity conductive packaging material and a preparation method thereof. Background Art

[0002] As the requirements for functionalization of modern electronic products and packaging materials continue to increase, the research on conductive packaging materials has gradually become an important topic in the field of materials science and engineering. Such materials not only need to have excellent conductive properties, but also need to meet the mechanical strength requirements in practical applications to withstand certain external stresses, tear resistance, compression resistance and other properties. Therefore, how to balance conductivity and mechanical strength has become a core problem in the design of conductive packaging materials. Zinc oxide (ZnO) has been widely used in the fields of nanotechnology and composite materials due to its good conductive properties, high chemical stability and rich surface reactivity. In particular, zinc oxide nanostructures, such as nanorods and nanoparticles, have unique physical and chemical properties that make them ideal candidates for improving the conductive properties of materials. However, existing zinc oxide materials often have problems such as poor dispersion of the polymer matrix and weak interface bonding during the composite process, which affects the comprehensive properties of its conductivity and strength.

[0003] In recent years, researchers have proposed a variety of solutions to the problem of balancing the conductivity and strength of materials. For example, by compounding metal nanoparticles or carbon-based materials such as graphene and carbon nanotubes with polymer materials, the conductivity is improved and the strength of the material is also enhanced. However, these methods usually face the dilemma that when the conductivity is improved, the mechanical properties of the material decrease. Therefore, how to ensure the mechanical strength of the composite material while maintaining or improving the conductivity is still a major challenge in the field of packaging materials.

[0004] Although some composite conductive packaging materials based on nanomaterials have been proposed and applied in actual production, these materials still have many deficiencies in performance. Traditional conductive packaging materials generally rely on metal particles, carbon-based materials, etc. as conductive fillers. Although these fillers can effectively improve conductivity, they often lead to poor mechanical strength of composite materials due to their own structural limitations or problems with bonding with the polymer matrix. Especially in the use of nano-scale fillers, the interface bonding between the filler and the polymer matrix is ​​insufficient, making the material prone to crack propagation and fracture during actual use.

[0005] As a semiconductor material with excellent electrical properties, zinc oxide has shown good electrical conductivity in many studies. However, traditional zinc oxide materials usually have problems with poor dispersion and loose interface bonding during the composite process, resulting in the failure to fully exert the conductive properties of the material. In addition, the purity and morphology of zinc oxide materials will directly affect their compatibility with polymers and the composite effect. Although some methods have been used to try to improve the performance of zinc oxide through doping and other means, these methods still have limitations. For example, doping elements may cause changes in the structure of zinc oxide, thereby affecting its stability and conductivity. In addition, in some high temperature or strong acid and alkali environments, the stability of these doped zinc oxide materials is poor, resulting in performance degradation, and they fail to fully meet the long-term use requirements of conductive packaging materials in harsh environments.

[0006] In current technology, there is still a lack of a solution that can effectively balance conductivity and mechanical strength. Most conductive packaging materials fail to effectively improve the mechanical properties of the material such as compression resistance and tear resistance when improving the conductivity, thus affecting its effect in actual packaging applications. Therefore, in the existing technology, how to improve the interfacial bonding force between zinc oxide nanorods and polymer matrix, enhance the overall performance of the composite material, and optimize its conductivity and strength at the same time is still a technical problem that needs to be solved urgently.

[0007] In order to solve the above problems, the present invention aims to provide a new type of high-strength and low-resistivity conductive packaging material. The material, by precisely regulating the structural characteristics of zinc oxide nanorods and the composite method of polyacrylic acid matrix, significantly improves its mechanical strength while ensuring the conductive performance of the material, especially in terms of compression and tear resistance. This technical solution can not only solve the balance problem between conductivity and strength of existing materials, but also improve the long-term stability and environmental adaptability of the material, thereby providing a more reliable solution for the practical application of conductive packaging materials. Summary of the invention

[0008] In order to achieve the above-mentioned purpose of the invention and to solve the above-mentioned technical problems, the present invention provides a method for preparing a high-strength and low-resistivity conductive packaging material. The specific scheme is as follows:

[0009] S1: cleaning the zinc oxide nanorods and uniformly dispersing them by ultrasonic vibration, dispersing the cleaned zinc oxide nanorods in deionized water, adding urea as a nitrogen source for nitrogen doping, washing the nitrogen-doped zinc oxide nanorods with deionized water and ethanol for multiple times, and finally drying them to obtain nitrogen-doped zinc oxide nanorods (N-ZnO);

[0010] S2 dissolves polyacrylic acid in deionized water and stirs until completely dissolved to obtain a polyacrylic acid solution;

[0011] S3: mixing nitrogen-doped zinc oxide nanorods with polyacrylic acid solution, adding dispersant sodium dodecylbenzene sulfonate, and uniformly dispersing them by ultrasonic vibration and stirring;

[0012] S4: coating the composite solution on the substrate, curing and drying to form a cured film.

[0013] Preferably, in step S1, the zinc oxide nanorods have a diameter of 50-100 nm and a length of 5-10 μm.

[0014] Preferably, in step S1, the concentration of urea as a nitrogen source is 0.1-0.2 mol / L.

[0015] Preferably, in step S1, the temperature of the nitrogen doping treatment is 300° C.-400° C., and the time is 2-3 hours.

[0016] Preferably, in step S1, the drying temperature of the nitrogen-doped zinc oxide nanorods is 80° C. and the drying time is 12 hours.

[0017] Preferably, in step S2, the mass concentration of the polyacrylic acid solution is 5%-10%, and the added amount of the dispersant is 0.5%-2% of the mass of the polyacrylic acid solution.

[0018] Preferably, in step S3, the mass ratio of the nitrogen-doped zinc oxide nanorods to polyacrylic acid is 1:3 to 1:5.

[0019] Preferably, in step S3, an ultrasonic processor is used to perform ultrasonic oscillation on the mixed solution for 30 minutes, and stirring is continued for 2 hours to ensure that the nitrogen-doped zinc oxide nanorods are uniformly dispersed in the polyacrylic acid matrix.

[0020] Preferably, in step S4, the curing temperature is 60° C. and the curing time is 6-8 hours.

[0021] The present invention also provides a high-strength and low-resistivity conductive packaging material, which is prepared by the above method.

[0022] The technical solution provided by the present invention brings beneficial effects:

[0023] Improve the balance between conductivity and strength of materials

[0024] By compounding nitrogen-doped zinc oxide nanorods with a polyacrylic acid matrix, the present invention significantly improves the strength and conductivity of the conductive material. Zinc oxide nanorods have high conductivity, and the nitrogen doping process enhances the conductivity of the zinc oxide nanorods and improves the interfacial bonding between the zinc oxide nanorods and the polymer matrix by introducing nitrogen elements. Nitrogen doping effectively increases the carrier concentration of zinc oxide, while avoiding the situation where the conductivity of pure zinc oxide is weakened due to the increase in the mechanical strength of the material. By accurately controlling the composite ratio of zinc oxide nanorods and the PAA matrix and the amount of dispersant used in the composite process, the present invention solves the common problems of insufficient strength and brittleness in the prior art while maintaining high conductivity, ensuring the compression resistance and tear resistance of the material in practical applications.

[0025] Optimize interfacial bonding and dispersion

[0026] The nitrogen-doped zinc oxide nanorods not only improve the conductivity of the zinc oxide nanorods by incorporating a nitrogen source, but also enhance their dispersibility in the polyacrylic acid matrix. Traditional zinc oxide materials often have problems of poor dispersibility and strong aggregation, resulting in unstable overall performance of the composite material. The present invention effectively improves the uniform distribution of zinc oxide nanorods in polyacrylic acid during the composite process by introducing a nitrogen source and using a dispersant, sodium dodecylbenzene sulfonate, thereby significantly improving the mechanical properties and conductive properties of the material. The use of ultrasonic oscillation further promotes the dispersion of zinc oxide nanorods in the polymer solution, avoids the problem of particle agglomeration and uneven distribution of the material after drying, and improves the overall stability and performance of the composite film.

[0027] Enhance the environmental stability and long-term performance of materials

[0028] The nitrogen-doped zinc oxide nanorods used in the present invention have high chemical stability and strong environmental adaptability. Zinc oxide has strong stability in high temperature, humid or extreme environments, and nitrogen doping further enhances its oxidation resistance, avoiding performance degradation caused by external environmental influences. Compared with traditional conductive materials, nitrogen-doped zinc oxide nanorods can effectively improve the stability of conductive packaging materials during long-term use, especially when exposed to humid or high temperature environments, and can maintain good conductivity and mechanical strength.

[0029] Improving the processing adaptability of composite materials

[0030] The composite method of the present invention has good processing adaptability. By reasonably controlling the composite ratio of nitrogen-doped zinc oxide nanorods and polyacrylic acid matrix, and using a suitable dispersant in the composite process, the common problem of poor bonding between nanomaterials and the matrix in the composite process is successfully overcome, so that the prepared composite material not only has excellent conductive properties, but also has high processing stability. In the film forming and curing process, the composite material has good coating and curing properties, ensuring the uniformity and high efficiency of the final material.

[0031] Improved conductivity stability during long-term use

[0032] The introduction of the nitrogen-doped zinc oxide nanorods into the composite material not only improves the electrical conductivity, but also effectively improves the electrical conductivity stability of the composite film during long-term use. Through reasonable process control, the electrical conductivity of the material is hardly affected by environmental factors (such as temperature and humidity) during use, so it can meet packaging applications with high requirements for long-term stability.

[0033] The composite conductive material has good electromagnetic shielding and antistatic properties and is particularly suitable for use as electronic component packaging material.

[0034] The composite material is suitable for applications such as anti-static and electromagnetic radiation shielding, and has broad application prospects, especially in electronic components, semiconductor equipment and packaging materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM photo of Comparative Example 2 of the present invention;

[0036] Figure 2 This is a SEM photo of Comparative Example 1 of the present invention;

[0037] Figure 3 This is a SEM photo of Example 1 of the present invention;

[0038] Figure 4 This is a schematic diagram of the conductive performance test of the present invention. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0040] Example 1

[0041] A method for preparing a high-strength and low-resistivity conductive packaging material, the implementation steps are as follows:

[0042] Synthesis of S1 Nitrogen-doped ZnO Nanorods

[0043] The diameter of the zinc oxide nanorods is 80 nm and the length is 8 μm. The zinc oxide nanorods are washed with ethanol to remove possible impurities on the surface, and the zinc oxide nanorod solution is ultrasonically vibrated for 15 minutes to ensure uniform dispersion.

[0044] Adding nitrogen source: Add urea as a nitrogen source into the reaction vessel, and the concentration of the nitrogen source is 0.2 mol / L.

[0045] Place the container in an electric furnace, set the temperature to 300°C, and maintain this temperature for 2.5 hours. Urea will undergo a thermal decomposition reaction at this temperature, decomposing into ammonia (NH3) and carbon dioxide (CO2), which will react with the zinc oxide nanorods to achieve nitrogen doping. Ensure that the temperature is stable and uniform during the reaction to ensure the nitrogen doping effect.

[0046] Cleaning and drying:

[0047] After the reaction was completed, the ZnO nanorods were washed several times with deionized water and ethanol to remove excess nitrogen sources and impurities.

[0048] Finally, the nitrogen-doped ZnO nanorods were dried at 80 °C for 12 h to ensure that they were dry and to remove moisture.

[0049] Preparation of S2 polyacrylic acid solution

[0050] Polyacrylic acid (PAA) powder was dissolved in deionized water to form a 5% PAA solution.

[0051] Stir the solution using a magnetic stirrer until the polyacrylic acid is completely dissolved and a homogeneous solution is formed.

[0052] Composite of S3 nitrogen-doped zinc oxide nanorods and PAA

[0053] Nitrogen-doped zinc oxide nanorods (N-ZnO) were composited with PAA solution, and the mass ratio of N-ZnO to PAA was 1:4.

[0054] Sodium dodecylbenzene sulfonate was added as a dispersant to the PAA solution in an amount of 1% of the mass of the polyacrylic acid solution to improve the dispersibility of the zinc oxide nanorods. The mixed solution was ultrasonically shaken for 30 minutes using an ultrasonic processor to ensure that the zinc oxide nanorods were evenly distributed in the polyacrylic acid matrix.

[0055] Continue stirring for 2 hours to ensure a uniform compound.

[0056] Step 4: Film formation and curing

[0057] The prepared composite solution was coated on a clean glass substrate and evenly coated using a blade.

[0058] Place in an oven at 60°C and dry for 6 hours until the composite film is completely dry and solidified.

[0059] Example 2

[0060] The preparation was carried out in the same manner as in Example 1, except that the concentration of the nitrogen source was 0.1 mol / L.

[0061] Example 3

[0062] The preparation is carried out in the same manner as in Example 1, except that the reaction temperature of doping in step S1 is 400°C.

[0063] Example 4

[0064] The preparation was carried out in the same manner as in Example 1, except that the mass ratio of N-ZnO to PAA was 1:3.

[0065] Example 5

[0066] The preparation was carried out in the same manner as in Example 1, except that the mass ratio of N-ZnO to PAA was 1:5.

[0067] Comparative Example 1

[0068] Preparation of polyacrylic acid solution

[0069] Polyacrylic acid (PAA) powder was dissolved in deionized water to form a 5% PAA solution.

[0070] Stir the solution using a magnetic stirrer until the polyacrylic acid is completely dissolved and a homogeneous solution is formed.

[0071] Film formation and curing

[0072] The prepared solution was applied onto a clean glass substrate and evenly coated using a blade.

[0073] Place in an oven at 60°C and dry for 6 hours until the composite film is completely dry and solidified.

[0074] Comparative Example 2

[0075] S1 ZnO Nanorods

[0076] The zinc oxide nanorods have a diameter of 80 nm and a length of 8 μm. The zinc oxide nanorods are washed with ethanol to remove impurities that may exist on the surface, and the zinc oxide nanorods are dried at 80° C. for 12 hours to ensure that they are dry and moisture is removed.

[0077] Preparation of S2 polyacrylic acid solution

[0078] Polyacrylic acid (PAA) powder was dissolved in deionized water to form a 5% PAA solution.

[0079] Stir the solution using a magnetic stirrer until the polyacrylic acid is completely dissolved and a homogeneous solution is formed.

[0080] Composite of S3 ZnO nanorods and PAA

[0081] The zinc oxide nanorods were compounded with the PAA solution, and the mass ratio of ZnO to PAA was 1:4.

[0082] Sodium dodecylbenzene sulfonate was added as a dispersant to the PAA solution in an amount of 1% of the mass of the polyacrylic acid solution to improve the dispersibility of the zinc oxide nanorods. The mixed solution was ultrasonically shaken for 30 minutes using an ultrasonic processor to ensure that the zinc oxide nanorods were evenly distributed in the polyacrylic acid matrix.

[0083] Continue stirring for 2 hours to ensure a uniform compound.

[0084] Step 4: Film formation and curing

[0085] The prepared composite solution was coated on a clean glass substrate and evenly coated using a blade.

[0086] Place in an oven at 60°C and dry for 6 hours until the composite film is completely dry and solidified.

[0087] Comparative Example 3

[0088] Synthesis of S1 Nitrogen-doped ZnO Nanorods

[0089] The diameter of the zinc oxide nanorods is 80 nm and the length is 8 μm. The zinc oxide nanorods are washed with ethanol to remove possible impurities on the surface, and the zinc oxide nanorod solution is ultrasonically vibrated for 15 minutes to ensure uniform dispersion.

[0090] Adding nitrogen source: Add urea as a nitrogen source into the reaction vessel, and the concentration of the nitrogen source is 0.2 mol / L.

[0091] Place the container in an electric furnace, set the temperature to 300°C, and maintain this temperature for 2.5 hours. Urea will undergo a thermal decomposition reaction at this temperature, decomposing into ammonia (NH3) and carbon dioxide (CO2), which will react with the zinc oxide nanorods to achieve nitrogen doping. Ensure that the temperature is stable and uniform during the reaction to ensure the nitrogen doping effect.

[0092] Cleaning and drying:

[0093] After the reaction was completed, the ZnO nanorods were washed several times with deionized water and ethanol to remove excess nitrogen sources and impurities.

[0094] Finally, the nitrogen-doped ZnO nanorods were dried at 80 °C for 12 h to ensure that they were dry and to remove moisture.

[0095] Preparation of S2 polyacrylic acid solution

[0096] Polyacrylic acid (PAA) powder was dissolved in deionized water to form a 5% PAA solution.

[0097] Stir the solution using a magnetic stirrer until the polyacrylic acid is completely dissolved and a homogeneous solution is formed.

[0098] Composite of S3 nitrogen-doped zinc oxide nanorods and PAA

[0099] Nitrogen-doped zinc oxide nanorods (N-ZnO) were composited with PAA solution, and the mass ratio of N-ZnO to PAA was 1:4.

[0100] The mixed solution was ultrasonically shaken for 30 minutes using an ultrasonic processor to ensure that the zinc oxide nanorods were evenly distributed in the polyacrylic acid matrix.

[0101] Continue stirring for 2 hours to ensure a uniform compound.

[0102] Step 4: Film formation and curing

[0103] The prepared composite solution was coated on a clean glass substrate and evenly coated using a blade.

[0104] Place in an oven at 60°C and dry for 6 hours until the composite film is completely dry and solidified.

[0105] Comparative Example 4

[0106] S1 carbon nanotubes

[0107] The diameter of the carbon nanotubes is 80 nm and the length is 8 μm. The carbon nanotubes are washed with ethanol to remove possible impurities on the surface, and the zinc oxide nanorods are dried at 80° C. for 12 hours to ensure that they are dry and moisture is removed.

[0108] Preparation of S2 polyacrylic acid solution

[0109] Polyacrylic acid (PAA) powder was dissolved in deionized water to form a 5% PAA solution.

[0110] Stir the solution using a magnetic stirrer until the polyacrylic acid is completely dissolved and a homogeneous solution is formed.

[0111] Composite of S3 carbon nanotubes and PAA

[0112] The carbon nanotubes were compounded with the PAA solution, and the mass ratio of the carbon nanotubes to the PAA was 1:4.

[0113] Sodium dodecylbenzene sulfonate was added as a dispersant to the PAA solution in an amount of 1% of the mass of the polyacrylic acid solution to improve the dispersibility of the carbon nanotubes. The mixed solution was ultrasonically shaken for 30 minutes using an ultrasonic processor to ensure that the carbon nanotubes were evenly distributed in the polyacrylic acid matrix.

[0114] Continue stirring for 2 hours to ensure a uniform compound.

[0115] Step 4: Film formation and curing

[0116] The prepared composite solution was coated on a clean glass substrate and evenly coated using a blade.

[0117] Place in an oven at 60°C and dry for 6 hours until the composite film is completely dry and solidified.

[0118] Experimental test:

[0119] 1. Conductivity test

[0120] Standard: Adopt the Chinese national standard GB / T 5206-2007 "Measurement method of electrical conductivity of electrical materials"

[0121] Test equipment: Four-probe resistivity tester

[0122] Test steps:

[0123] Prepare a composite film sample of 5 cm × 5 cm

[0124] The surface resistivity of the sample was measured using the four-probe method

[0125] Test temperature: room temperature (25°C)

[0126] Test humidity: relative humidity is 50%

[0127] Test schematic diagram Figure 4

[0128] 2. Tensile strength and tensile modulus test

[0129] Test standards and methods:

[0130] Standard: Adopting the Chinese national standard GB / T 1040-2006 "Test method for tensile properties of plastics"

[0131] Test steps:

[0132] Prepare composite film samples with a size of 20 mm × 10 mm

[0133] Carry out tensile test on the testing machine and set the tensile speed to 5mm / min

[0134] Measure the tensile strength and tensile modulus of the sample and record the data

[0135] Test conditions: Test temperature: room temperature (25°C)

[0136] 3. Tear strength test

[0137] Test standards and methods:

[0138] Standard: Adopt the Chinese national standard GB / T 1963-2005 "Test method for tear strength of plastic film".

[0139] Testing equipment: Tensile testing machine with tearing fixture

[0140] Test steps:

[0141] Prepare composite film samples with a size of 10 mm × 100 mm

[0142] The tear strength was measured and recorded.

[0143] Test conditions: Test temperature: room temperature (25°C)

[0144] Table 1 Experimental data summary

[0145]

[0146] 1. Conductivity analysis (surface resistivity)

[0147] The nitrogen-doped zinc oxide nanorod composite materials in the examples all exhibited low surface resistivity under different preparation conditions, indicating their excellent electrical conductivity. The surface resistivity of Example 1 was the lowest, only 0.045Ω·cm, which was significantly better than that of Comparative Examples 1, 2, 3 and 4, reflecting the significant advantages of the present invention in improving electrical conductivity. The introduction of nitrogen-doped zinc oxide nanorods effectively improved the electrical conductivity of the composite material, especially by optimizing the doping conditions and the composite ratio, improving the performance of the material in electrical applications.

[0148] 2. Tensile strength

[0149] The tensile strength of Example 1 is 35.2 MPa, which is significantly improved compared to other samples in the comparative experiment. Even under the conditions of Example 2 (31.4 MPa) and Example 3 (33.8 MPa), it is significantly better than the comparative experimental samples. Through the composite of nitrogen-doped zinc oxide nanorods, the material of the present invention not only improves the conductivity, but also improves the mechanical strength of the material, especially in application scenarios with high strength requirements, showing better tensile strength.

[0150] 3. Tensile modulus

[0151] In terms of tensile modulus, the composite materials in the examples also exhibit superior performance. Example 1 (850 MPa) has significant advantages over the comparative experimental material, and the tensile modulus is still much higher than the comparative experimental sample. The improved tensile modulus shows that the present invention has also achieved a good balance in terms of material rigidity and structural stability, and can maintain strong load-bearing capacity and deformation resistance in practical applications.

[0152] 4. Tear strength

[0153] The tear strength test results further verify the excellent performance of the material of the present invention. The tear strength of Example 1 is 12.8N / mm, which is significantly higher than that of the comparative experimental material. The material of the present invention also shows advantages in tear resistance, enabling it to maintain good durability when used for a long time and exposed to environmental conditions.

[0154] 5. SEM photos

[0155] Figure 2 In order to dope a certain amount of zinc oxide nanorod composite materials, it can be clearly observed that the polyacrylic acid composite material Figure 1 The base presents a rod-shaped three-dimensional network structure. Figure 3 It can be seen that after the addition of nitrogen-doped zinc oxide nanorods, the three-dimensional network structure of the composite material becomes more obvious, and the rods are entangled with each other to form a skeleton, which increases the porosity of the material structure and is more conducive to the effective conduction of electrons or ions inside the material.

[0156] Overall advantages: The materials provided by the present invention show significant improvements in conductivity, tensile strength, tensile modulus and tear strength compared with the comparative materials, especially achieving a good balance between the strength and conductivity of the composite material. Beneficial effects: Through the introduction of nitrogen-doped zinc oxide nanorods and combined with appropriate composite processes, the present invention not only improves the conductivity of the material, but also greatly enhances its mechanical strength and tear resistance. This greatly improves the stability, durability and practical application adaptability of the material in long-term use, and is particularly suitable for use in the packaging field that requires high conductivity and strength.

[0157] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength, low-resistivity conductive packaging material, characterized in that: The following steps are involved: S1: cleaning the zinc oxide nanorods and uniformly dispersing them by ultrasonic vibration, dispersing the cleaned zinc oxide nanorods in deionized water, adding urea as a nitrogen source for nitrogen doping, washing the nitrogen-doped zinc oxide nanorods with deionized water and ethanol for multiple times, and finally drying them to obtain nitrogen-doped zinc oxide nanorods (N-ZnO); S2 dissolves polyacrylic acid in deionized water and stirs until completely dissolved to obtain a polyacrylic acid solution; S3: mixing nitrogen-doped zinc oxide nanorods with polyacrylic acid solution, adding dispersant sodium dodecylbenzene sulfonate, and uniformly dispersing them by ultrasonic vibration and stirring; S4: coating the composite solution on the substrate, curing and drying to form a cured film.

2. The method for preparing a high-strength, low-resistivity conductive packaging material according to claim 1, characterized in that: In step S1, the zinc oxide nanorods have a diameter of 50-100 nm and a length of 5-10 μm.

3. The method for preparing a high-strength, low-resistivity conductive packaging material according to claim 1, characterized in that: In step S1, the concentration of urea as a nitrogen source is 0.1-0.2 mol / L.

4. The method for preparing a high-strength, low-resistivity conductive packaging material according to claim 1, characterized in that: In step S1, the temperature of the nitrogen doping treatment is 300° C.-400° C., and the time is 2-3 hours.

5. The method for preparing a high-strength, low-resistivity conductive packaging material according to claim 1, characterized in that: In step S1, the nitrogen-doped zinc oxide nanorods are dried at a temperature of 80° C. for 12 hours.

6. The method for preparing a high-strength, low-resistivity conductive packaging material according to claim 1, characterized in that: In step S2, the mass concentration of the polyacrylic acid solution is 5%-10%, and the added amount of the dispersant is 0.5%-2% of the mass of the polyacrylic acid solution.

7. The method for preparing a high-strength, low-resistivity conductive packaging material according to claim 1, characterized in that: In step S3, the mass ratio of the nitrogen-doped zinc oxide nanorods to polyacrylic acid is 1:3 to 1:

5.

8. The method for preparing a high-strength, low-resistivity conductive packaging material according to claim 1, characterized in that: In step S3, an ultrasonic processor is used to perform ultrasonic vibration on the mixed solution for 30 minutes, and stirring is continued for 2 hours to ensure that the nitrogen-doped zinc oxide nanorods are uniformly dispersed in the polyacrylic acid matrix.

9. The method for preparing a high-strength, low-resistivity conductive packaging material according to claim 1, characterized in that: In step S4, the curing temperature is 60° C. and the curing time is 6-8 hours.

10. A high-strength, low-resistivity conductive packaging material, characterized in that: The packaging material is prepared by any method according to claims 1-9.